THE ASPECT OF THE CONTRACT LAW REFORM WITHIN THE REGULATION OF INDONESIA - Wagian, Diangsa (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The research aims to study the aspect of the contract law reform within the virous regulations living in Indonesia. To obtain the purpose, the research is conducted through a legal normative study. It simultaneously applies to statute, conceptual, and case approaches. This research is conducted through a literature study towards the relevan legal materials. The results of the research elaborated in a descriptive and analytic way using qualitative methods to analyze the data. The research discovers that the norms of Contract law as stipulated in the Book III of Indonesian Code Civil have been gradually and continuously reformed by Indonesian governments since 1960. The reform is carried out partially and spread in various regulation as explained above. Therefore, nowadays in Indonesia, the contract law not only exists in the Book III of Indonesian Code Civil but also in various relevant regulations. The reform has been conducted by the government by breaking through one of the very basic principle and the backbone of contracts law, is that the freedom of contract. As a result, parties in contract have no more absolute freedom to contract or to determine the clauses of contract. Such policy made by government to protect public interest and inferior or subordinate party in a contract. Thus, the contract law nowadays shows that it is not purely private anymore but containing public aspect, where penal and administrative laws penetrate to it. Key Words: Legal Reform, Contract Law, Regulation